COMPREHENSIVE METHODOLOGY FOR TRANSLATION ANALYSIS OF CROSS-CULTURAL INCONGRUITY IN ENGLISH ANECDOTES - Oleksandr S. Sodel (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2023)
The article substantiates the problem of performing translation analysis of cross-cultural incongruity in English anecdotes in Ukrainian translation using the methodology consisting of four methodological blocks (qualification, linguocultural, linguistic, and translation ones). The purpose of the article is to justify the presented cognitive and discursive methodology for translation analysis of cross-cultural incongruity when transferring the comic in English anecdotes into Ukrainian. The tasks of the research are the following: to characterize the methods of linguistic and cultural analysis in the study of the ethnocultural specificity of the conceptual picture of the world embodied in English anecdotes; to describe the methods of linguistic analysis of verbal means of expressing the comic in English anecdotes; to analyze the strategies and tactics of rendering the comic in Ukrainian translation of English anecdotes. The research material is taken from anecdotes in translation, presented in the collections Awesome Jokes by S. Keller and the resource 1001 Jokes by R. Wiseman on the Internet site, which were rendered into Ukrainian mostly by amateur translators, and in which comic effect was adequately represented in translation. 1112 anecdotes were studied, including 807 context realization of key concepts of the comic in original and translation. The research methodology of translation analysis of cross-cultural incongruity in English anecdotes during their translation into Ukrainian, in addition to the application of general scientific methods of analysis, synthesis, systematization, and induction, relies on the methodological base of linguocultural studies, cognitive linguistics, and translation studies. The cognitive and discursive nature of the research determines the choice of presentation of the research methodology in the form of methodological blocks, which include qualification, linguistic and cultural, linguistic and translation blocks. The qualification methodological block is a selection of relevant empirical material and general characterization of the phenomenon of the comic from the perspective of linguocultural, linguistic, and translation studies aspects of the incongruity of the English anecdote and supposes the method of continuous sampling. Further, the study of crosscultural incongruity caused by the ethnocultural features of the conceptual worldviews of the English and Ukrainian peoples presupposes the use of methods of linguocultural analysis constituting the linguocultural methodological block: the method of cultural and historical analysis, linguocultural analysis, interpretive and textual analysis, conceptual analysis, comparative analysis. Cross-cultural incongruity caused by the systemic and structural features of the linguistic world pictures of Englishmen and Ukrainians determines the use of methods of linguistic analysis in the linguistic methodological block: methods of contextual, distributive, component, and linguostylistic analysis. The study of the means of translation of verbal means of creating the comic in the translations of anecdotes into Ukrainian determines applying translational and transformational analysis which constitute the translation methodological block. The article argues that using the described methodology consisting of four methodological blocks (qualification, linguocultural, linguistic, and translation ones) allows us to draw the regularities in solving the problem of cross-cultural incongruity when translating English anecdotes into Ukrainian, thus connecting the type of incongruity with the means of its representation in translation.